The role of the cell cycle in the cellular uptake of folate-modified poly(l-amino acid) micelles in a cell population. Issue 48 (14th October 2015) - Tang, Jihui; Liu, Ziwei; Ji, Fenqi; Li, Yao; Liu, Junjie; Song, Jian; Li, Jun; Zhou, Jianping
Abstract : Nanoparticles are widely recognized as a vehicle for tumor-targeted therapies. Abstract : Nanoparticles are widely recognized as a vehicle for tumor-targeted therapies. There are many factors that can influence the uptake of nanoparticles, such as the size of the nanoparticles, and/or their shape, elasticity, surface charge and even the cell cycle phase. However, the influence of the cell cycle on the active targeting of a drug delivery system has been unknown until now. In this study, we initially investigated the folate receptor α (FR-α) expression in different phases of HeLa cells by flow cytometric and immunocytochemical methods. The results obtained showed that FR-α expression was cell cycle-dependent, i.e. the S cells' folate receptor expression was the highest as the cell progressed through its cycle. Then, we used folate modified poly(l -amino acid) micelles (FA-PM) as an example to investigate the influence of the cell cycle on the active targeting drug delivery system. The results obtained indicated that the uptake of FA-PM by cells was influenced by the cell cycle phase, and the S cells took up the greatest number of folate conjugated nanoparticles. Our findings suggest that future studies on ligand-mediated active targeting preparations should consider the cell cycle, especially when this system is used for a cell cycle-specific drug.